Influence of dietary Moringa oleifera on broilers performance, intestinal microbial population and humoral immune competence - ABD EL-GHANY, W.A.; ERAKY, R.D. (Journal of the Hellenic Veterinary Medical Society, 2020)
This study was designed to evaluate the effect of using different levels of phytobiotic containing Moringa oleifera (M. oleifera) leaf powder (MOLP) on broiler chickens body growth performance parameters, intestinal microbial population, and the humoral immune response. Day-old Hubbard broiler chicks (n = 200) were randomly allocated into 4 treatment diet. Basal diet was supplied with treatments T0, T1, T2 and T3 representing (0, 1%, 5% and 7.5% MOLP); respectively. Chickens were kept under observation for 5 weeks. Body performance parameters, total viable bacterial and coliform counts and humoral immune response to Newcastle disease (ND) virus vaccine were detected using the haemagglutination inhibition (HI) test. The results revealed significant (P < 0.05) improvement in performance parameters in groups supplemented with dietary MOLP. However, the best significant (P < 0.05) performance was observed in the group fed 1% MOLP. There was no significant (P < 0.05) difference among treatments considering the total viable intestinal bacterial and coliform counts. Significant (P < 0.05) increase in the means of HI in dietary MOLP supplemented groups was observed, where the highest means were seen in 1% MOLP treated birds. In conclusion, dietary supplementation with MOLP could improve the performance parameters and the immune response while reducing the total viable intestinal bacterial and coliform counts of broiler chickens. The study recommended using of dietary level of 1% MOLP to improve performance, intestinal health, and immune competence.